Assessing Student Attitudes Towards Volunteerism at Public Higher Education Institution - Abu Bakar, Hatinah; Abdull Rahim , Mohd Faisal; Tajuddin , Haida Suraya; Othman , Nurul Nadia; Noor Asmawi, Muhammad Nurhafiz; Mohamad Basri, Arash Idham; Yusainiamin, Nur Fitrisha Emylda (International Journal of Accounting, Finance and Business, 2025)
The purpose of this research is to identify the level of attitudes and spirit of volunteerism among students in UiTM Cawangan Kelantan. This study also obtains to examine the significance influence between attitude and spirit volunteerism among students. Moreover, this study also examines the comparison between genders in relation to the attitude toward volunteerism and the level of spirit of volunteerism. A total of 179 students that completed the questionnaires. The data employed reliability, independent t-test and regression analysis. The study showed that the level of attitude and spirit towards volunteerism among student are positive. Moreover, even though, females show a slightly more positive attitude toward volunteerism than males, the difference is not statistically significant. The finding also indicates that significant relationship between attitude and spirit of volunteerism among students. For further research, it is recommended using other dimensions of factors such as knowledge and religiosity to the study.